PENGARUH PEMBERIAN PUPUK KOMPOS APUAPU TERHADAP PERTUMBUHAN DAN HASILTERUNG (Solanum melongena L.) - Aritka Diun Pratama; Ince Raden; Mohamad Fadli (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2022)
This study aims to determine the effect of kompos apu-apu on the growth and yield of eggplant. This study started from December 2017 to March 2018. Located in the Sumber Sari Village, Loa Kulu District, Kutai Kartanegara Regency. This research is compiled using a Randomized Completely Block Design (RCBD) consisting of four replications and consists of seven levels, that is: k0 : 0 (control), k1 (5 t ha-1), k2 (10 t ha-1), k3 (15 t ha-1), k4 (20 t ha-1), k5 (25 t ha-1), k6 (30 t ha-1). The results showed that compost fertilizer had no significant effect on plant height and plant age when flowering, number of plants, crop weight, and fruit weight per hectare. Treatment k6 (30 t ha-1) gave the highest average yield of 5,63 t ha-1. The treatment of k0 (control) gave the lowest average yield of 2,55 t ha-1).